L-shaped association between oxidative balance score and vision-related functional burden in adults in the United States, NHANES 2005–2008 - Li, Juntong; Ye, Sheng; Li, Xiang; Liu, Hui; Yang, Yue; Lu, Xuelei; Jin, Heyue; Liu, Li (Frontiers in Nutrition, 2025)
ObjectiveThis study aims to investigate the relationship between oxidative balance score (OBS) and vision-related functional burden (VRFB) in US adults.MethodsThe study utilized data from two consecutive cycles of the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2008. A multivariate weighted logistic regression model was employed to explore the relationship between OBS and VRFB in the general population and subgroups, while the interaction effects were tested with a likelihood test. Restricted cubic spline was utilized to assess the nonlinear association of OBS with VRFB. Sensitivity analyses were performed to test the robustness of the results.ResultsA total of 6,682 participants aged 20 years and older were included in the NHANES database. A negative association between OBS and VRFB was observed in the fully adjusted model, with an odds ratio (OR) of 0.968 [95% confidence interval (CI): 0.949–0.987]. Compared with the lowest quartile of OBS, the second (OR: 0.669, 95%CI: 0.486–0.922), the third (OR: 0.589, 95%CI: 0.403–0.859), and highest (OR: 0.554, 95%CI: 0.359–0.855) quartiles of OBS were associated with a reduced risk of VRFB. An L-shaped association was displayed between OBS and VRFB (P for nonlinear = 0.016). Notably, when the analysis was stratified by employment status, a significant interaction between OBS and VRFB was observed (P for interaction < 0.05). The protective effect of OBS was more pronounced among the unemployed. The results were found to be robust in sensitivity analyses.ConclusionThis study found an L-shaped relationship between OBS and VRFB among U.S. adults aged 20 years and older. This novel finding suggests that maintaining a favorable oxidative balance through modifiable dietary and lifestyle (such as increased physical activity, smoking cessation, reduced alcohol consumption) may help protect functional vision. We also observed a stronger negative association between OBS and VRFB among the unemployed. This study provides new insights into the prevention of functional vision loss, highlighting the importance of not only dietary and lifestyle factors but also considering different subgroups, such as the unemployed. Further longitudinal studies are required to further validate these observations and elucidate the underlying mechanisms, particularly in elucidating causal relationships among variables, controlling for confounding factors, and examining the development of visual function.